2007
DOI: 10.1111/j.1528-1167.2006.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Neocortical and Thalamic Spread of Amygdala Kindled Seizures

Abstract: Summary:Purpose: Amygdala kindling is an epilepsy model involving long-term network plasticity in the nervous system. In this model, repeated weak stimulation of the amygdala eventually leads to severe motor seizures. The mechanisms for worsening behavioral seizures, and the possible role of enhanced connectivity between the amygdala and other structures have not been thoroughly investigated.Methods: We performed simultaneous field potential recordings from the amygdala, frontal cortex, and medial thalamus dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 53 publications
7
32
0
Order By: Relevance
“…Another explanation is that the more extensive inter-hemispheric synaptic connections between extra-temporal lobe regions facilitate the spread or propagation of epileptic activity between these hemispheres when the focus is in these regions. This is supported by evidence from EEG-fMRI studies (Yu et al, 2009;Kobayashi et al, 2006) (Tyvaert et al, 2008) as well as human and animal data (Keller and Roberts, 2008;Blumenfeld et al, 2007); (Holmes et al, 1999;Zilles et al, 1998;Silva-Barrat et al, 1986) which show regional as well as distant cortical and subcortical changes associated with focal interictal spikes, being more so in patients with extra-temporal foci. It also would correlate well with the described increased incidence of bilateral features in extra-temporal lobe seizure semiologies (Luders et al, 1998;Gastaut, 1970) and of bilateral interictal and ictal discharges seen in patients with extra-TLE (Bautista et al, 1998;Taylor et al, 2003;Gibbs and Gibbs, 1955) as opposed to TLE where most reports show that even if bilateral interictal discharges are recorded, they are predominant over the side with seizure onset in 60-70% of patients (Hirsch et al, 1991;Williamson et al, 1993).…”
Section: Groupmentioning
confidence: 55%
“…Another explanation is that the more extensive inter-hemispheric synaptic connections between extra-temporal lobe regions facilitate the spread or propagation of epileptic activity between these hemispheres when the focus is in these regions. This is supported by evidence from EEG-fMRI studies (Yu et al, 2009;Kobayashi et al, 2006) (Tyvaert et al, 2008) as well as human and animal data (Keller and Roberts, 2008;Blumenfeld et al, 2007); (Holmes et al, 1999;Zilles et al, 1998;Silva-Barrat et al, 1986) which show regional as well as distant cortical and subcortical changes associated with focal interictal spikes, being more so in patients with extra-temporal foci. It also would correlate well with the described increased incidence of bilateral features in extra-temporal lobe seizure semiologies (Luders et al, 1998;Gastaut, 1970) and of bilateral interictal and ictal discharges seen in patients with extra-TLE (Bautista et al, 1998;Taylor et al, 2003;Gibbs and Gibbs, 1955) as opposed to TLE where most reports show that even if bilateral interictal discharges are recorded, they are predominant over the side with seizure onset in 60-70% of patients (Hirsch et al, 1991;Williamson et al, 1993).…”
Section: Groupmentioning
confidence: 55%
“…Progressive mossy fiber sprouting is a well-known ultrastructural change, which has been observed in kindling, and may contribute to abnormal excitability by forming recurrent excitatory synapses in the dentate gyrus (Sutula and Dudek 2007). On a network level, kindling results in increased connectivity as measured by both ictal and interictal EEG signal coherence between limbic and neocortical regions, specifically between the amygdala and the frontal cortex and medial thalamus (Blumenfeld and others 2007). GABA(A) receptor density is progressively increased in the dentate gyrus and acutely downregulated but chronically upregulated in CA1 and CA3 (Liu and others 2009).…”
Section: Kindling Modelmentioning
confidence: 99%
“…The performance of the commonly used WOSA coherence estimator may be extremely poor for small values of nd, and the coupling of poor estimation and statistical testing can result in inaccuracy in the measurement of MSC. In our previous work we have described the statistical properties of the coherence estimator [13], defined upper bounds of the effect of a scalp reference electrode on coherence measurements of icEEGs [14], and demonstrated the utility of this measure for measuring network change [2]. Fig 1(a) displays, in a single patient with right MTLE, all pairs of electrode contacts with delta MSC > 0.6.…”
Section: Studymentioning
confidence: 98%
“…Pairwise measures of relationship have been used to study seizures and the peri-seizure interval, typically in studies of seizure spread, seizure onset, and seizure prediction, and on interictal or background icEEG (ongoing activity between seizures). In a recent study of the background icEEG we demonstrated increased long-range theta coherence, between amygdala and the frontal lobe, accompanies the process of kindling in a rat model of epilepsy [2]. Further, Towle and coworkers, used the coherence of the background icEEG to define the functional borders of brain regions [3].…”
Section: Introductionmentioning
confidence: 97%